Vascular smooth muscle cell FTO deletion aggravates atherosclerotic plaque instability by promoting VSMC migration through the N6-methyladenosine modification of the COL3A1 mRNA - Zhiliang Yang; Keyong Deng; Jiani Wu; Naqiong Wu; Zhifan Li; Shuang Yang; Mengyi Sun; Dan Liu; Xiaotong Ning; Shufeng Chen; Bin Yang; Jue Ye; et al. (Science China Life Sciences, 2026)

FACMamba: Frequency-Aware Coupled State Space Modeling for Underwater Image Enhancement - Li Wang; Keyong Shen; Haiyang Sun; Xiaoling Cheng; Jun Zhu; Bixuan Wang (Journal of Marine Science and Engineering, 2025)
Recent advances in underwater image enhancement (UIE) have achieved notable progress using deep learning techniques; however, existing methods often struggle with limited receptive fields, inadequate frequency modeling, and poor structural perception, leading to sub-optimal visual quality and weak generalization in complex underwater environments. To tackle these issues, we propose FACMamba, a Mamba-based framework augmented with frequency-aware mechanisms, enabling efficient modeling of long-range spatial relations for underwater image restoration. Specifically, FACMamba incorporates three key components: a Multi-Directional Vision State-Space Module (MVSM) to model directional spatial context via the proposed 8-direction selective scan block (SS8D), a Frequency-Aware Guidance Module (FAGM) for learning informative frequency representations with low overhead, and a Structure-Aware Fusion Module (SAFM) to preserve fine-grained structural cues through adaptive multi-scale integration. Recognizing the importance of spatial-frequency interaction, our model fuses these representations via lightweight architecture to enhance both texture and color fidelity. Experiments on standard UIE benchmarks demonstrate that FACMamba achieves a favorable balance between enhancement quality and computational efficiency, outperforming many existing UIE methods.

Mechanical properties optimization of edible clove oil/chitosan composite materials by multi-island genetic algorithm for active fresh-keeping packaging applications - Hui Liu; Zhenhua Yin; Cuiyun Liu; Mengxuan Cao; Jianming Sun; Xiaofang Wang; Keyong Tang; Xinchang Pang (Food Packaging and Shelf Life, 2025)

Comparison of biosynthetic astaxanthin with other sources: effects on growth, pigmentation, and environmental stress resistance in Pacific white shrimp, Litopenaeus vannamei - Yingrui Sun; Mei Liu; Keyong Jiang; Chen Zhong; Yan Gao; Baojie Wang; Lei Wang (Aquaculture International, 2025)

Design of efficient dispase one-bath strategy with low pollution and life cycle assessment for eco-sustainable leather processing - Hui Liu; Zhenhua Yin; Mengya Li; Cuiyun Liu; Muhammad Amir Ali; Jie Liu; Jianming Sun; Keyong Tang; Xinchang Pang (Journal of Environmental Chemical Engineering, 2025)

Uncovering chromatin accessibility and cancer diagnostic potential via cell-free DNA utilization - Jie Li; Jiahui Chen; Xin Sun; Heli Yang; Keyong Sun; Chang Liu; Yongwang Wang; Mengyue Xu; Xin Ji; Ji Zhang; Xiaojiang Wu; Anqiang Wang; et al. (Science Bulletin, 2024)

Contrasting fluids and implications for ore genesis in the Jiawula-Chaganbulagen Porphyry Mo-epithermal Pb Zn metallogenetic system: Evidence from fluid inclusions and H-O-He-Ar isotopes - LiXue Sun; Wenyuan Wang; Gang Li; Keyong Wang; Wenju Li; Feng Tian; Zhigao Wang (Geochemistry, 2024)

DPOI: Distributed software system development platform for ocean information service - Zhongwen Guo; Keyong Hu; Yongguo Jiang; Zhaosui Sun (Journal of Ocean University of China, 2015)

Molecular Cloning of Hemocyanin cDNA from Fenneropenaeus chinensis and Antimicrobial Analysis of Two C-terminal Fragments - Chuwen Qiu; Jie Sun; Mei Liu; Baojie Wang; Keyong Jiang; Shujuan Sun; Xiaolin Meng; Zuoyong Luo; Lei Wang (Marine Biotechnology, 2014)